Biomechanical Analysis of Intra-articular Pressure After Coracoclavicular Reconstruction. (January 2017) - Voss, Andreas; Singh, Hardeep; Dyrna, Felix; Buchmann, Stefan; Cote, Mark P.; Imhoff, Andreas B.; Mazzocca, Augustus D.; Beitzel, Knut
Background: Recent biomechanical and clinical studies have demonstrated the effectiveness of suture button and pulley-type fixations for surgical treatment of acromioclavicular instability. Concerns remain that such procedures can "overconstrain" (overreduce the lateral clavicle in relation to the acromion to a nonphysiological position) the joint. Purpose/Hypothesis: The purpose of this study was to investigate the intra-articular pressure of native and reconstructed acromioclavicular (AC) joints in relation to the configuration of the joint. Anatomic (0 mm), overconstrained (−3 mm), and underconstrained (+3 mm) AC joint reconstructions were simulated. The hypothesis was that reconstructions using suture pulley systems do not increase the intra-articular pressure of the AC joint. Study Design: Controlled laboratory study. Methods: Eleven fresh-frozen cadaveric shoulders were used in this study (mean age ± SD, 60.8 ± 6.7 years). Each specimen underwent radiographic analysis by using a Zanca view to determine the basic configuration of the AC joint. A pressure Tekscan sensor was inserted in the AC joint. A servohydraulic materials testing system was used for testing. The specimens were kept in the testing machine, and the native AC position was marked at 0 mm. This allowed moving the clavicle during the surgical procedure with reference to the native anatomic position. Intra-articular pressure in the native AC joint during cyclic loading (1000 cycles; 1 Hz) was measured. After native testing, the AC ligaments and coracoclavicular ligaments were cut and reconstructed using a cortical button technique. Anatomic, −3 mm, and +3 mm positions, relative to the acromion, were cyclically loaded, and intra-articular pressure was documented. Results: According to the AC joint classification of inclination, we identified five type 1 (46%), four type 2 (36%), one type 3 (9%), and one incongruous (9%) configurations. Changes in superior displacement across the 4 conditions were not statistically significant (0.5 ± 0.8 [native], 0.01 ± 0.00 [0 mm repair], 0.02 ± 0.02 [−3 mm repair], and 0.01 ± 0.01 [+3 mm repair]; P = .162). Before testing (time point 1), pressure in the −3 mm repair (62.9 ± 70.1) differed between the native state (11.3 ± 21.8; P = .042) and the +3 mm repair (7.1 ± 18.4; P = .023). All other changes at time points 2 (after cyclic loading unloaded) and 3 (after cyclic loading loaded) in pressure were not significant. ( P = .086 and .226, respectively). Conclusion: AC joint reconstruction (within −3 to +3 mm of reduction) with a coracoclavicular suture button device does not significantly increase the intra-articular pressure of the AC joint after cyclic loading in our experimental cadaveric setup. Clinical Relevance: Recent biomechanical and clinical studies have demonstrated the effectiveness of suture button and pulley-type fixations for coracoclavicular reconstruction of the joint. Concerns remain that such procedures would "overconstrain" the joint because of the high rigidity of these pulley systems and the preservation of the lateral clavicle. This overconstraining may potentially result in pain at the lateral end of the clavicle, osteolysis, or a later increased risk of early osteoarthritis. Therefore, our results indicate that within a range of ±3 mm to the anatomic position, overconstraining may not result in a higher intra-articular pressure.